2015
DOI: 10.3382/ps/pev286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rice bran on performance, egg quality, oxidative status, yolk fatty acid composition, and fatty acid metabolism-related gene expression in laying ducks

Abstract: The study was designed to evaluate the effects of different dietary levels of rice bran (RB) in laying duck diets on performance, egg quality, oxidation status, egg yolk fatty acid composition, and hepatic expression of fatty acid metabolism-related genes. Longyan females (1080) with similar BW at 19 wk of age were randomly assigned to 6 dietary treatments, each consisting of 6 replicates of 30 birds. The basal diet (I) was a typical corn-soybean ration while the experimental diets (II to VI) substituted RB fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…As presented in Table 4 no differences were observed across the treatments regarding feed conversion ratio, live weight changes and egg mass. These results are in accordance with those of Ruan et al [17]. Furthermore, no specific feed refusal due to the wheat bran containing diets was observed during the experiment, as daily feed intakes did not differ.…”
Section: Laying Performance Parameters and General Egg Qualitysupporting
confidence: 92%
“…As presented in Table 4 no differences were observed across the treatments regarding feed conversion ratio, live weight changes and egg mass. These results are in accordance with those of Ruan et al [17]. Furthermore, no specific feed refusal due to the wheat bran containing diets was observed during the experiment, as daily feed intakes did not differ.…”
Section: Laying Performance Parameters and General Egg Qualitysupporting
confidence: 92%
“…This may be attributed to the higher ME content in their diet because full-fat rice bran contains higher ME than DFRB. Furthermore, rice bran contains high amounts of phytates (12.8 g/kg compared to 2.0 g/kg in corn) and non-starch polysaccharides (NSPs), which are not digested by poultry and are mostly excreted [18]. Studies have shown that high NSP content in the diet adversely affects the growth performance of broilers [19,20].…”
Section: Growth Performancementioning
confidence: 99%
“…Under the trend of increasing global demand for corn, poultry producers are being forced to seek local raw materials to replace corn in animal feed. A large number of researchers have investigated the effect of different feed ingredients on the performance of poultry such as rice bran [ 1 , 2 ], defatted rice bran [ 3 , 4 ], paddy rice [ 5 , 6 , 7 ], whole wheat [ 8 , 9 , 10 ] and millet [ 11 , 12 , 13 ]. China is the largest rice producer in the world, accounting for 27.63% of global rice production [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of broken rice on serum biochemical variables of geese at 70 days of age1 . Each value represents the mean of six replicates.…”
mentioning
confidence: 99%